Vibro-Acoustics of Lightweight Sandwich Structures - Lu, Tianjian (Springer Tracts in Mechanical Engineering, 2014)
Vibro-Acoustics of Lightweight Sandwich Structures introduces the study of the coupled vibration and acoustic behavior of lightweight sandwich structures in response to harmonic force and sound pressure. This book focuses on the theoretical modeling and experimental investigation of lightweight sandwich structures in order to provide a predictive framework for vibro-acoustic characteristics of typical engineering structures. Furthermore, by developing solution tools, it concentrates on the influence of key systematic parameters leading to effective guidance for optimal structure design toward lightweight, high-stiffness and superior sound insulation capability. This book is intended for researchers, scientists, engineers and graduate students in mechanical engineering especially in structural mechanics, mechanics and acoustics. Fengxian Xin and Tianjian Lu both work at the School of Aerospace, Xiâ_Tan Jiaotong University.